(untitled) (Italian Journal of Public Health, 2008)
Background: The outbreak of vector-associated diseases is determined by different factors. One of them is the existence of appropriate climatic conditions which influence the development of vectors as well as pathogens. Nowadays, accurate data on the occurrence of both vectors and pathogens are often not available in Germany, espite the coastal zones of Lower Saxony (Germany) being former malaria regions. Thus, the question arises, whether a new autochthonous transmission could take place due to the monthly mean temperatures of recent ears taking into consideration the predicted increase in air temperatures according to the IPCC scenarios. Methods: To model areas at risk, the transmission potential for new tertian malaria spreads in respect to emperature was computed in a GIS environment using the Basic Reproduction Rate (R0) formula. Results:We were able to corroborate that the risk of tertian malaria transmission is increasing as temperature s the determining variable of the mathematical model. Conclusions: Lower Saxony is at risk of a new outbreak of tertian malaria assuming no other risk factors than emperature being of relevance.